Nodular Histiocytic Hyperplasia: A Rare Manifestation of Asbesto Exposure - Storch, Layni (2020)
A nodular hyperplasia histiocytic (HNH) is a rare condition, with no preference for gender or age, marked by a benign proliferative process, sometimes confused with malignant neoplasia, consisting mostly of histiocytes (1, 2). Local chronic inflammation and mechanical irritation are among the main causes postulated for this entity. Malignant pathologies, on the other hand, represent the main differential diagnoses, or that highlight the clinical importance of theirassertive diagnosis, being an immunohistochemistry an important diagnostic tool (3). In this article, the authors describe a case of pulmonary pulmonary histiocytic hyperplasia in a non-smoking male patient with a history of asbestos exposure or the likelihood of inciting a chronic inflammatory process with histiocytes proliferation. The patient has dyspnea, pleuritic pain and hemoptysis and recurrent hemorrhagic pleural effusion following death due to exacerbation of symptoms. Although the entity is used in the literature as a benign histiocytic cell proliferation, there are rare cases related to the evolution and treatment of the disease. Key words: Histiocytic nodular hyperplasia, asbestos, pleura, lung.